Exploring the relationship between multi-morbidity, resilience and social connectedness across the lifecourse. (May 2014) - Ong, Bie Nio; Richardson, Jane C; Porter, Tom; Grime, Janet
Multi-morbidity is receiving considerable attention in public policy, health and social care. From the perspective of the individual, multi-morbidity is a more complex experience than solely having a clinical diagnosis. In this article, we will argue that understanding multi-morbidity can be facilitated by considering the relationship between adversity (in this case multi-morbidity), resilience and social connectedness within a life course framework. This provides an approach that can capture the dynamics of social relationships, social connectedness and the fluctuations in the experience of multi-morbidity. We draw on a qualitative study of 17 people who have multiple conditions, but consider themselves as being able to maintain a sense of identity and self over time and in the face of adversity. From their accounts, a more varied picture emerges of living with multi-morbidity. This then depicts a more realistic representation of how each person shapes their multi-morbidity and resilient responses within their own social context, which can help to formulate more effective ways of supporting them.